FTA Utilization in the Philippines: Trends and Determinants - Francis Mark A. Quimba; Neil Irwin S. Moreno; Abigail E. Andrada (Philippine Institute for Development Studies (PIDS), 2022)
The Philippines has adopted free trade agreements (FTAs) as a major component of its trade policy in the last two decades. As it continues to pursue trade liberalization through joining these agreements, taking a closer look to the extent of FTA utilization in the country is important. This study attempted to reveal stylized facts on the trends of Philippine FTA utilization. Using the universe of trade transactions data, FTA utilization trends were observed both from the export and import perspectives. Throughout the 2010s, FTA utilization among exporters has been low; in contrast, utilization in imports has been expanding. The calculated utilization rates also revealed that Philippine imports have considerably utilized FTAs, with the exception of imports from Japan, South Korea, and Singapore. The study also identified key determinants of FTA use among Philippine manufacturing firms, using a micro data set that merged the trade transactions data with the firm survey/census data. Results of the regression analysis suggest the significance of acquiring sufficient productivity levels, as well as knowledge and experience on international trade activities, in firm FTA use. It was also notable that foreign ownership was a positive determinant of FTA use in exports, while exhibiting negative estimates on FTA import use. The state of competition at the industry level could negatively affect a firm's decision to use FTAs, while larger preferential tariff margins could persuade firms to trade under FTA schemes. With regard to the Philippine FTA policy, the findings of this study highlight the need to focus on stimulating FTA use among Philippine firms.
Keywords: 330; FTA utilization; self-selection; matched data; firm knowledge